ECONOMETRIC ASSESSMENT OF THE VOLUME OF RETAIL TRADE IN THE TRADING SYSTEM - Makhmatkulov, Golibjon Kholmuminovich (THE INNOVATION ECONOMY, 2026)
This article assesses the dynamics of changes in the volume of regional retail trade in the process of developing the trade system. The study analyzes the dynamics of retail trade in the Republic of Uzbekistan and Kashkadarya region for 2010-2024 based on statistical and trend methods. In addition, it analyzes the methodological foundations of the development of marketing activities in the retail system in modern conditions. The study considered the issues of forming marketing strategies based on an in-depth study of the domestic market, consumer behavior, market segmentation and the competitive environment.The results of the study provide an opportunity to improve the mechanisms of regional development of the trade system and optimize the regional trade system